2007
DOI: 10.4319/lo.2007.52.2.0609
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal shifts in chemotype composition of Microcystis sp. communities in the pelagial and the sediment of a shallow reservoir

Abstract: The various oligopeptides produced by individual Microcystis clones enable the classification of individual colonies of Microcystis in distinct peptide chemotypes. The dynamics and diversity of coexisting chemotypes are regarded as major factors influencing the microcystin-content of blooms of this potentially toxic cyanobacterial genus. We compared the chemotype composition in planktonic and benthic Microcystis communities in Brno reservoir (Czech Republic) from July to November 2004 by single-colony mass spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
58
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 40 publications
2
58
1
Order By: Relevance
“…Field studies have indicated that different Microcystis morphotypes may show different ecostrategies in the field (36). MrpC, as a potential colony type-specific factor, may be highly important for the competitive advantage of specific Microcystis ecotypes in the field.…”
Section: Discussionmentioning
confidence: 99%
“…Field studies have indicated that different Microcystis morphotypes may show different ecostrategies in the field (36). MrpC, as a potential colony type-specific factor, may be highly important for the competitive advantage of specific Microcystis ecotypes in the field.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it seems that the changes in microcystin contents during the development of Microcystis blooms are due to a seasonal succession of toxic and nontoxic strains, in which nontoxic strains prevail at the height of the Microcystis bloom. A seasonal succession of toxic and nontoxic Microcystis geno-or chemotypes has indeed been observed in several lakes (11,53).…”
mentioning
confidence: 98%
“…Microcystis populations often consist of mixtures of microcystin-producing and non-microcystin-producing strains (10,23,48,52). Interestingly, several studies show that the average microcystin content expressed per cell is typically high at the onset of Microcystis blooms but much lower at the height of these blooms (22,51,53). In other words, with increasing Microcystis biomass, the Microcystis cells become, on average, less toxic.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although some studies have explained the decrease of cyanobacterial biomass by cyanophage (lysis viruses) (Yoshida et al, 2006), predatory bacteria (Mayali and Azam, 2004) in the water column and/or sedimentation of the population (Visser et al, 1995;Welker et al, 2007), the degenerative process in water blooms is still not thoroughly understood. The stage of decline 38 Vol.30 CHIN.…”
Section: Introductionmentioning
confidence: 99%